Comparative analysis of Meissner's corpuscles in the fingertips of primates - Verendeev, Andrey (J Anat, 2015)
Meissner's corpuscles (MCs) are tactile mechanoreceptors found in the glabrous skin of primates, including fingertips. These receptors are characterized by sensitivity to light touch, and therefore might be associated with the evolution of manipulative abilities of the hands in primates. We examined MCs in different primate species, including common marmoset (Callithrix jacchus,n = 5), baboon (Papio anubis,n = 2), rhesus macaque (Macaca mulatta,n = 3), chimpanzee (Pan troglodytes,n = 3), bonobo (Pan paniscus,n = 1) and human (Homo sapiens,n = 8). Fingertips of the first, second and fourth digits were collected from both hands of specimens, dissected and histologically stained using hematoxylin and eosin. The density (MCs per 1 mm(2)) and the size (cross-sectional diameter of MCs) were quantified. Overall, there were no differences in the densities of MCs or their size among the digits or between the hands for any species examined. However, MCs varied across species. We found a trend for higher densities of MCs in macaques and humans compared with chimpanzees and bonobos; moreover, apes had larger MCs than monkeys. We further examined whether the density or size of MCs varied as a function of body mass, measures of dexterity and dietary frugivory. Among these variables, only body size accounted for a significant amount of variation in the size of MCs.